2012
DOI: 10.1002/star.201200094
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the production of a maltooligosaccharides producing amylase from the alkalophilic Streptomyces lonarensis strain NCL 716 using SVR Modeling

Abstract: The Streptomyces lonarensis strain NCL 716 hydrolyses starch to produce a mixture of maltotriose (G3) and maltotetraose (G4) along with maltose (G2). The objective of the present work was to determine an optimum cost effective media composition for the production of α‐amylase from this strain. The most influential factor was found to be starch while the least influential factor found was peptone by Plackett–Burman method. Peptone amount was kept constant throughout the fermentation. Peptone, which is one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In accordance with the literature, in this study, yeast extract was observed to induce high amylase production of 68.06 U/mL. Sharma et al (2013) investigated the optimization of the production of amaltooligosaccharides producing amylase. Similar to our results the most influential factor was found to be yeast extract while the least influential factor found was peptone.…”
Section: Production Of α-Amylase From Bacillus Subtilis Sdp1supporting
confidence: 77%
See 1 more Smart Citation
“…In accordance with the literature, in this study, yeast extract was observed to induce high amylase production of 68.06 U/mL. Sharma et al (2013) investigated the optimization of the production of amaltooligosaccharides producing amylase. Similar to our results the most influential factor was found to be yeast extract while the least influential factor found was peptone.…”
Section: Production Of α-Amylase From Bacillus Subtilis Sdp1supporting
confidence: 77%
“…The manufacture of small maltooligosaccharides is not easy, and the search for microbial enzymes that specifically act on starch substrate to produce specific maltooligosaccharides has gained importance (Sharma et al, 2013). There are a few amylases (Kuddus et al, 2012) that specifically produce such maltooligosaccharides at mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It uses the support vectors to define the hyperplane which maps the relationship between the response and independent variables. The SVRs minimize generalized error rather than the training error thus avoiding the problem of overfitting (Sharma et al, ). SVR has gained popularity in recent years as an alternative to the ANNs as it possesses the ability to model complex non‐linear relationships using less computational space.…”
Section: Introductionmentioning
confidence: 99%
“…Streptomyces spp NAA-28 Biotechnology Food, paper, detergent, fermentation, textile, and pharmaceutical sectors [51] Streptomyces griseus (SGAmy) medicine Antibiofilm agent [52] Streptomyces lonarensis NCL 716 Food Maltooligosaccharides production [53] Streptomyces erumpens MTCC 7317 Food Soluble starch and cassava starch hydrolysis [54] Streptomyces enissocaesilis NRRL B-16365 Food High fructose corn syrup production [55] Streptomyces spp Food Bakery [56] Streptomyces spp SNAJSM6 Biotechnology α-amylase production [57]…”
Section: Industry Application Referencesmentioning
confidence: 99%